2008
DOI: 10.1017/s0029665108006976
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and cancer

Abstract: The prevalence of obesity, defined as a BMI of ‡ 30 . 0 kg/m 2 , has increased substantially over previous decades to about 20 % in industrialized countries, and a further increase is expected in the future. Epidemiological studies have shown that obesity is a risk factor for: postmenopausal breast cancer; cancers of the endometrium, colon and kidney; malignant adenomas of the oesophagus. Obese subjects have an approximately 1 . 5-3 . 5-fold increased risk of developing these cancers compared with normal-weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
203
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(216 citation statements)
references
References 224 publications
(269 reference statements)
6
203
2
5
Order By: Relevance
“…The risk of colorectal cancer development is increased in obese individuals, possibly due to elevated activity of biologically active substances produced by the fat tissue (Pischon et al 2008). The adipokine leptin has been implicated in colorectal cancer development and progression due to its mitogenic, anti-apoptotic, mitogenic, and pro-inflammatory activity (Garofalo & Surmacz 2006, Karagiannides & Pothoulakis 2007, Ratke et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of colorectal cancer development is increased in obese individuals, possibly due to elevated activity of biologically active substances produced by the fat tissue (Pischon et al 2008). The adipokine leptin has been implicated in colorectal cancer development and progression due to its mitogenic, anti-apoptotic, mitogenic, and pro-inflammatory activity (Garofalo & Surmacz 2006, Karagiannides & Pothoulakis 2007, Ratke et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adipocytes and preadipocytes can stimulate the growth of colon cancer cells (Amemori et al 2007). Furthermore, biologically active substances produced by adipocytes, such as cytokines (especially pro-inflammatory), growth factors, steroid hormones can exert oncogenic effects in the large bowel (Karagiannides & Pothoulakis 2007, Pischon et al 2008, Pais et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a key risk factor for a number of metabolic disorders, including type 2 diabetes, dyslipidaemia and cardiovascular disease, and has been associated with increased mortality [1][2][3][4][5][6]. Although the exact biological mechanisms linking obesity to these comorbidities are not fully understood, it has been shown that increased adiposity, especially abdominal fat accumulation, over time leads to a cluster of metabolic and cardiovascular abnormalities, including elevated blood glucose, insulin resistance, raised triacylglycerol, lower HDL-cholesterol and high BP [7,8].…”
mentioning
confidence: 99%
“…Most health experts agree that a BMI of 30?0 kg/m 2 represents the upper limit of a healthy weight (18) . A BMI of $ 30?0 kg/m 2 is associated with increases in the prevalence of CVD (19) , stroke (20) , atherosclerosis (21) , hypertension (22) , diabetes (23) , arthritis (24) and several cancers (25) . Just as with the food disappearance data, the obesity data can be divided into two linear components -one beginning in 1960 and ending around 1980 and the other continuing from 1980.…”
mentioning
confidence: 99%